Survey on the salt usage among fish cracker (keropok lekor) manufacturers in several districts of Kuala Terengganu, Malaysia - Qurratul Aeina Faizi Faizul; Suzana Shahar; Zaliha Harun; Mohd Noor Hidayat Adenan; Hasnah Haron (Penerbit Universiti Kebangsaan Malaysia, 2024)
Fish crackers (keropok lekor) are known for their tastiness. Although rich in protein and iodine, it contains a high amount of salt or sodium. Therefore, this study aimed to determine the manufacturers’ practice in the preparation of keropok lekor, perception and challenges concerning salt usage, and motivation to reduce salt content. This study also aimed to estimate the sodium content in keropok lekor. Seven manufacturers of keropok lekor in Terengganu were interviewed either face-to-face or online to obtain relevant information. All interviews were recorded, transcribed, and analyzed based on a thematic analysis framework. The recipes of keropok lekor were analyzed using the Nutritionist Pro software to determine the nutritional and sodium content, calculated based on the Malaysian and ASEAN Food Composition Tables. Based on the interviews, most manufacturers (90%) supported the effort to reduce salt in keropok lekor. However, the effort was met with several challenges, such as customer acceptance and negative perception of the taste, decreased sales, and increased material costs. The enabling factors include maintaining the original flavor of keropok lekor, customer requests, marketing opportunities, and the availability of salt substitutes. Support for marketing and financial technology know-how is also necessary. An estimate of 606.43 mg/100g of sodium content in keropok lekor was obtained in this study, which was mainly derived from the usage of sodium chloride and monosodium glutamate (MSG) during the preparation. This study revealed the high salt content in keropok lekor due to the addition of salt and seasonings. There is a potential to reduce salt content in keropok lekor with appropriate support provided to the manufacturers. Nevertheless, further research is needed to produce keropok lekor with reduced salt content, improved sensory, and enhanced microbial and physicochemical characteristics, which can improve customer perception.